Keterlibatan Tuanku dalam Pergesekan Identitas Adat, Agama, dan Negara di Minangkabau - Wimra, Zelfeni (Universitas Islam Negeri Raden Intan Lampung, 2020)
Tuanku in Minangkabau culture is a reflection of how these institutions are involved in the nation-state political process and religious mission. This article describes his involvement in the endless identity friction between state, religious and adat actors. Data were collected using a social network analysis method that highlights Tuanku's identity through a genealogical approach. In addition, interviews were optimized to confirm prior critical sociological research. The formulation of al-'urf is also used to interpret the crossing of normative and cultural texts. The results of this study indicate that Tuanku's involvement in Minangkabau largely determines the quality of the success of the state and religion in realizing their political and missionary strength. The implication is to recognize important points that are known in the friction of these three elements of identity, so that they can be useful for the development of knowledge in the field of Islamic law and social science.